Crafting new traditions : Canadian innovators and influences - Egan, Melanie; Johnson, Jean; Elder, Alan C., 1955- (Book collections on Project MUSE., 2008)
"Crafting New Traditions: Canadian Innovators and Influences brings together the work of 11 historians and craftspeople to address the two questions of "who has influenced the recent history of Canadian studio craft?" and "who will be considered the 'pioneers' of Canadian craft in the future?""--Jacket.